Teaching by design : using your computer to create materials for students with learning differences - Voss, Kimberly S. 4 0 16; 5 (Bethesda, MD : Woodbine House, 2005)
Presents step-by-step instructions for using a computer to create more than forty customized educational materials designed to help children and adults with cognitive, sensory, or physical disabilities improve their visual perception, math, language, communication, writing, and self-help skills.
Includes index.
Professional.
Keywords: 2 -- 0; 6; Education;Audio-visual aids.;Aids and devices;Computer-aided design.;Education.;Aids and devices. -- Learning disabled children;Teaching;Remedial teaching.;Learning disabled children;Teaching; 20; 2